HUBUNGAN ANTARA MINAT SISWA DAN HASIL BELAJAR BAHASA INGGRIS MEREKA DI SMA NEGERI UJUNGBATU - Sri Dewi Mulyani; Mahdum '; Syofia Delfi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study is aimed to find out the correlation between students’ interest and their English learning achievement at SMA Negeri Ujungbatu. The problem needs to be discussed in this research is: is there any correlation between students’ interest and their English learning achievement at SMA Negeri Ujungbatu. The population of this research was the first grade students of SMA Negeri Ujungbatu which was 527 students. The writer used random sampling technique to choose the sample. There were 263 students chosen as the samples of this research. The instruments of the research were questionnaire which was related to the students’ interest in learning English and documentation of their English learning achievement which assessed by using Product Moment’s formula that were analyzed by using SPSS 17.0 statistics program. Based on the Product Moment test, it shows that there is significant and positive correlation between students’ interest and their English learning achievement of the first grade students at SMA Negeri Ujungbatu indicating a high correlation. Therefore, it answered the research question that there is a correlation between students’ interest and their English learning achievement. This study suggests the students to build more interest in learning English because interest and learning achievement has a positive relationship, the teachers to make the English lesson more interesting because it can influence students’ interest while studying English and other researchers to conduct a specific language skill because this research refers to some skills in English.Key words: Correlation, interest, english learning achievement